Theology for a Scientific Age Being and Becoming - Natural and Divine - Peacocke, A. R. (Arthur Robert) (Minneapolis Fortress Press, 1993)
"Enlarged edition."Originally published: Oxford ; Cambridge, Mass. : B. Blackwell, 1990, in series: Signposts in theology. Includes bibliographical references (p. [350]-432) and index. Contents: The theological and scientific enterprises -- 'Science and
Keywords: Religion and science. Theology, Doctrinal